Educational mobile game design for children learning mathematics - Mahdi, Shakir Mahmood (2017)
Children can learn while playing computer educational games. Therefore, it is important that educational games for children are well designed and usable. This study proposes an educational mobile game design for children to learn mathematics. Based on the design, a low fidelity and high fidelity prototypes called PreMath Operations were designed and developed. A usability evaluation was conducted on the prototypes by observing children playing with the games. The result of the evaluation suggested that PreMath Operations prototypes is usable and can help children to learn math while playing. This study provides a design strategy of mathematic educational game for children to learn in a fun and interesting